ASSYRIOLOGY AT THE MARGINS, THE CASE OF WILLIAM ST. CHAD BOSCAWEN (1855–1913)1. Issue 1 (5th January 2016) - Horry, Ruth
Abstract : This study presents the career of late-nineteenth-century Assyriologist William St. Chad Boscawen (1855–1913) as a case study in recovering contributions to knowledge-making by low-status, marginal actors. Boscawen took Assyriological knowledge and expertise, gained at the British Museum, into a new disciplinary setting: a private museum of history of medicine, owned by pharmaceuticals entrepreneur Henry Wellcome (1853–1936). Yet his relocation was only partially successful, and his contributions to knowledge were transient. I employ a sociological framework to explore how social factors, as much as academic ones, influenced Boscawen's career trajectory. In doing so, I argue that studying marginal figures offers a richer understanding of past Assyriological practices and the wider research community in which the most prominent figures operated.